Authenticity of Honey: Characterization, Bioactivities and Sensorial Properties - Escuredo, Olga; Seijo, M. Carmen (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Honey is a very complex food that requires multiple analytical, statistical and mathematical methods to guarantee honey authentication. This Special Issue contains innovative research on different analytical procedures for the determination of chemical compounds, functional properties, sensory characteristics and pollen profiles for the interpretation of the botanical and geographical origin of honey. This book compiles twelve original studies that address these issues and improve the knowledge of honeys of multiple botanical and geographical origins.